2005
DOI: 10.1097/01.pec.0000159055.49683.cd
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade Presenting as an Apparent Life-Threatening Event

Abstract: The initial emergency department (ED) evaluation of infants with an apparent life-threatening event (ALTE) often fails to identify a definitive cause for the event. Many children that present with an ALTE appear normal by the time they arrive to the ED. These factors can desensitize clinicians into prematurely discounting serious underlying causes of the ALTE or being less prompt in their evaluation of these patients. We present the case of a young infant who presented to an ED with an ALTE resulting from card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Others suggested that ALTEs may indicate underlying sepsis, pertussis, physical abuse, arrhythmias, metabolic diseases, seizures, or even cardiac tamponade. [6][7][8][9][10][11] The SIDS rate for infants with ALTEs who required cardiopulmonary resuscitation was found to be 10% in one study, and it increased to 28% with multiple ALTEs. 11 On the basis of these studies, it became common practice to view infants presenting with an ALTE as being at high risk, to admit them to the hospital for a diagnostic evaluation, and to consider discharge with home apnea/bradycardia monitoring.…”
mentioning
confidence: 94%
“…Others suggested that ALTEs may indicate underlying sepsis, pertussis, physical abuse, arrhythmias, metabolic diseases, seizures, or even cardiac tamponade. [6][7][8][9][10][11] The SIDS rate for infants with ALTEs who required cardiopulmonary resuscitation was found to be 10% in one study, and it increased to 28% with multiple ALTEs. 11 On the basis of these studies, it became common practice to view infants presenting with an ALTE as being at high risk, to admit them to the hospital for a diagnostic evaluation, and to consider discharge with home apnea/bradycardia monitoring.…”
mentioning
confidence: 94%
“…3 Tachypnea has a sensitivity of 87% to 89% and has frequently been described in the pediatric literature. 10,11 It should particularly raise concern in the setting of clear pulmonary fields on auscultation and imaging. JVD is almost always present in euvolemic adult patients 3 but is much less commonly seen in children 10,11 and has an overall sensitivity of 76%.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 It should particularly raise concern in the setting of clear pulmonary fields on auscultation and imaging. JVD is almost always present in euvolemic adult patients 3 but is much less commonly seen in children 10,11 and has an overall sensitivity of 76%. 9 Regardless of age, JVD is unreliable if a patient is hypovolemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation